Al Rizky Laundry Business Development Strategy for Small and Medium Enterprises (MSMEs) - Al Farisi, Muhammad Salman; Rahmi, Vembri Auliah (Dinasti Publisher, 2025)
This research delves into the business development strategies employed by Al Rizky Laundry, employing a combination of SWOT analysis and Business Model Canvas (BMC). The primary objective of this research is to assess the internal and external factors influencing the company’s performance through the SWOT analysis methodology. The qualitative research approach was selected to delve into the intricate understanding of complex phenomena pertinent to the development of Al Rizky Laundry’s business strategy. Specifically, SWOT analysis was employed to identify the company’s strengths, weaknesses, opportunities, and threats, leading to the formulation of four distinct strategies. Furthermore, Business Model Canvas (BMC) analysis was conducted to identify critical business elements that can be leveraged to enhance the company’s competitiveness and operational efficiency. The findings of this study offer a comprehensive understanding of the factors that influence the success of Al Rizky Laundry’s development strategy. The proposed recommendations from the SWOT analysis, along with each BMC element identified as an input for the development of the Al Rizky Laundry business, are compiled by considering the strengths of Al Rizky Laundry and future development opportunities. This step aims to address existing weaknesses and anticipate potential business challenges. With the implementation of the recommendations, Al Rizky Laundry’s development strategy is centered around five fundamental principles designed to enhance competitiveness, expand market reach, and deliver an exceptional customer experience. Based on the analysis conducted, Al Rizky Laundry possesses substantial potential to address its current shortcomings through a diverse range of innovative strategies. Recommendations include enhancing its social media presence, implementing a digital payment system, modernizing its equipment, and developing a digital-based management system. Furthermore, establishing strategic partnerships with online motorcycle taxi platforms and institutions such as Islamic boarding schools can substantially expand its market reach.